Molecular biology of beta-estradiol-estrogen receptor complex binding to estrogen response element and the effect on cell proliferation - Heger, Zbynek; Zitka, Ondrej; Krizkova, Sona; Beklova, Miroslava; Kizek, Rene; Adam, Vojtech (Neuro endocrinology letters, 2013)
Group of estrogen pollutants, where the highest estrogen activity is reported at estradiol, is characterized by the fact that even at very low concentrations have potential to cause xenoestrogenic effects. During exposure of excessive amounts of estradiols may be produced undesirable effects resulting in the feminization of males of water organisms. The presence of estradiols in drinking water implies also a risk for the human population in the form of cancers of endocrine systems, abnormalities in reproduction or dysfunctions of neuronal and immune system. Currently, the research is focused mainly to uncover the relationship between the estrogen receptors binding affinity with an estrogen response element and estradiol. In this review we summarized facts about molecular biological principles of β estradiol-estrogen receptor complex binding with estrogen response element and its successive effect on cancer genes expression.
Keywords: Receptors, Estrogen; Animals; vazba proteinů; Response Elements; Humans; proliferace buněk; regulace genové exprese; lidé; Gene Expression Regulation; zvířata; mužské pohlaví; Estradiol; Male; Protein Binding; receptory pro estrogeny; responzivní elementy; estradiol; Cell Proliferation